The relation between mental health problems and future violence among detained male juveniles - Olivier F. Colins; Thomas Grisso (BMC, 2019)
Abstract Background Detention personnel may assume that mental health problems heighten the likelihood of future violence in detained youth. This study explored whether brief mental health screening tools are of value for alerting staff to a detained youth's potential for future violent offending. Method Boys (n = 1259; Mean age = 16.65) completed the Massachusetts Youth Screening Instrument-Second Version (MAYSI-2) and the Strengths and Difficulties Questionnaire (SDQ) as part of a clinical protocol. Official records were collected to index past and future violent offending. Results A few significant positive and negative relationships between MAYSI-2 and SDQ scale scores and future violent offending were revealed, after controlling for age, past violent offending, and follow-up time. These relations were almost entirely dissimilar across the ethnic groups, even to the extent of finding opposite relations for boys in different ethnic groups. Conclusions The small number of relations and their small effect sizes suggest little likelihood that screening for mental health problems in boys who are detained in the Netherlands offers any potential for identifying youth at risk for committing future violent crimes. The current findings also suggest that ethnic differences in the relation between mental health problems and future criminality must be considered in future studies.